PAL - A Language for Multiple-Precision Algorithms - Hagerup, Torben (DAIMI Report Series, 1983)
Traditional notations (programming languages) are seldom adequate for the description of multiple-precision computations. This is because there is no way to specify how accurately the arithmetic operations should be carried out. This paper presents a special-purpose programming language which allows multiple-precision algorithms to be stated accurately and elegantly.